The Role of Pedagogical Skills in Attracting the Attention of Students (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Mastery is perceived as a teacher and educator's most important professional quality. The teacher organizes the educational process, achieving the required level of education, development and knowledge of students. The teacher plays the role of a mentor, a senior friend, and a participant in joint educational activities.